2013
DOI: 10.1016/j.jhydrol.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Variation of organic carbon and nitrate with river flow within an oceanic regime in a rural area and potential impacts for drinking water production

Abstract: International audienceOver the last two decades, climate change has become a major environmental and public health concern due to the increase of the mean temperature on the Earth and its consequences on extreme meteorological events such as floods and droughts. These events induce very low or very high river flows that may impair surface water quality, and therefore result in potential health impacts when used for drinking water production. The present study aims at assessing the impact of hydrologic regime o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 37 publications
3
12
1
Order By: Relevance
“…For example, Baurès et al (2013) demonstrated a relationship between DOC and NO 3 − that was positive, and thus opposite compared with our study, during high flow rates. Therefore, further studies should consider not only base flow conditions but also event water.…”
Section: Wavelet Analysiscontrasting
confidence: 93%
See 1 more Smart Citation
“…For example, Baurès et al (2013) demonstrated a relationship between DOC and NO 3 − that was positive, and thus opposite compared with our study, during high flow rates. Therefore, further studies should consider not only base flow conditions but also event water.…”
Section: Wavelet Analysiscontrasting
confidence: 93%
“…This fact might help to realign previous findings of other researchers on different correlations at varying scales, e.g., Taylor and Townsend (2010) on global negative correlations and Baurès et al (2013) on a positive correlation at short timescales during high flow rates.…”
Section: Discussionsupporting
confidence: 53%
“…Because point sources were absent, these results suggested reduced input from non‐point sources during low‐flow periods. Evidence for reduced loads during low‐flow due to changed water origin compared to normal conditions was also found elsewhere (Baures et al, ; Burt & Worrall, ; Burt, Worrall, Howden, & Anderson, ; Foster & Walling, ; Morecroft, Burt, Taylor, & Rowland, ; Zielinski, Gorniak, & Piekarski, ).…”
Section: Introductionsupporting
confidence: 67%
“…Many studies reported higher water temperatures during low-flow periods (Baures et al, 2013;Chessman & Robinson, 1987;Hanslík, Marešová, Juranová, & Vlnas, 2016;Sprague, 2005;van Vliet & Zwolsman, 2008;Zielinski et al, 2009). On the one hand, increased water temperatures intensify biological activity, particularly, primary production releasing oxygen and taking up nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Mosley (2015) reviewed and integrated efforts that studied drought impacts on the water quality of freshwater systems. Most studies concluded that water temperature increased during hydrological drought episodes (Baures et al, 2013;Ha, Cho, Kim, & Joo, 1999;Hanslík, Marešová, Juranová, & Vlnas, 2016;Van Vliet & Zwolsman, 2008), whereas two studies observed no significant changes in water temperature (Mosley et al, 2012;Wilbers, Zwolsman, Klaver, & Hendriks, 2009). Higher water temperature intensifies biological activity, leading to more oxygen release.…”
mentioning
confidence: 99%